Rancang Bangun Sistem Informasi Lelang Agunan Di PT. BPRS Al-Salaam Amal Salman Berbasis Web - Ahmad Syarif Maulana A; Ardianto Moenir (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. BPRS Al Salaam Amal Salman is engaged in Sharia Banking. Currently, the process of selling the collateral items from the customer is through an internal auction at each branch. In this research, the system development method uses the waterfall method. data collection methods are observation, interviews, and literature study. For the design stage using UML (Unified Modeling Language) can analyze input data and output data. PHP (Hypertext Preprocessor) as the programming language and MySQL / MariaDB as the database. Testing is done by the Blackbox method. The test results can meet the needs desired by PT. BPRS Al Salaam Amal Salman can market the auctioned collateral to the public space, facilitate its use, record every collateral sold or unsold, and can make reports in real-time to the head office. It also makes it easier for prospective auction customers to find out information on the collateral being auctioned and make a price offer for the auction collateral they want to own without having to come to the branch office.